The importance of hand hygiene in pre-adolescent health: an experience report (Research, Society and Development, 2021)
The pre-adolescent phase is marked by several psychosocial changes, so it is necessary to positively sensitize the daily practices of this group. Hand hygiene is an essential practice in the health of the general population, so it is undoubtedly necessary to introduce such a routine in the life of pre-adolescents. The objective of this work is to report the experience of nursing students in a health education action carried out in a public school, with the theme of alternative forms of hand hygiene based on the reality experienced by this group. The methodology used was the problematization theory proposed by Berbel, in addition to an explanation about the theme and a quiz with prizes to increase the interest of young people about work. The results obtained were considered taking into account the change in habit that was soon noticed by the researchers. With this, we see the importance of taking health education to the community and thus minimizing the problems experienced by the population.